Behavioural Problems in Children with 46XY Disorders of Sex Development - Nalini M. Selveindran; Syed Zulkifli Syed Zakaria; Muhammad Yazid Jalaludin; Rahmah Rasat (International Journal of Endocrinology)
The aim of this study is to determine the behavioural problems of children with 46XY disorders of sex development (DSD) with genital ambiguity and to identify the risk factors that may influence behaviour. The 27 participants (aged 6–18 years) consisted of 21 patients raised as boys and 6 patients raised as girls. Control data were obtained from a representative sibling of each patient who was matched for age and gender. The study tool used was the Child Behaviour Checklist (CBCL), which is a parent-administered questionnaire. The analysis of the behavioural scores revealed that the patient group had poorer scores in the total, externalizing, and internalizing realms. This group also had poorer scores in the anxious-depressed, social, and rule-breaking realms as compared to the control group. In addition, the XY-F group had higher scores (more pathological) than the XY-M group, although the difference in the scores was not statistically significant. A comparison of the prevalence of patients with scores in the clinical range with that of the control group was not statistically significant. These findings support the current recommendations that psychological counselling should be an integral part of the professional support offered to patients with DSD.